Grammatiktheorie und Empirie in der germanistischen Linguistik - Wöllstein, Angelika; Krifka, Manfred; Habermann, Mechthild; Gallmann, Peter (Germanistische Sprachwissenschaft um 2020, 2018)
The volume takes stock of grammatical theory and empiricism in Germanic linguistics, presenting critical discussions of issues related to paradigms, methods, and objectives. The essays cover themes such as descriptive completeness and grammatical modeling that have shaped recent discourse in the field. They also shed light on lacunae, thus opening up new research perspectives in the discipline.